Motorized Vehicle Security System Using SMS with GPS Tracking Method Based on Arduino UNO - Prasetio, Andhika Dwi; Aji, Wahyu Sapto (Signal and Image Processing Letters, 2025)
Cases of motorcycle loss are increasingly common in the community. This situation is caused by the lack of security systems installed on motorcycles, which are generally limited to the vehicle's ignition key. In fact, only a few medium-sized motorcycles are equipped with alarms as an additional form of security. A solution is needed to reduce theft or robbery on motorized vehicles, which is realized through a study entitled "Motorized vehicle security system using SMS with GPS Tracking method based on Arduino UNO A system that uses GPS and SMS that can be found on smartphones. This system is able to control the connection and disconnection of electric current in motorized vehicles using SMS, then it will be forwarded to the relay. The motorized vehicle security system using SMS with the Arduino UNO-based GPS Tracking method that has been made can function properly and can detect the position of the motorcycle accurately according to the motorcycle coordinate point. Tests to detect the position of the vehicle were carried out as many as 20 locations and the results were in accordance with the coordinate points of the vehicle. In testing to turn off the motorcycle engine, the results show that the motorcycle can be turned off remotely with an average delay of 6.97 seconds. In testing to turn on and turn off the alarm, the results show that the motorcycle alarm can be turned off remotely with an average delay of 7 seconds. this shows that the motorized vehicle security system using SMS with the Arduino UNO-based GPS Tracking method that has been made can function properly and as it should.